Desenvolvimento e aplicação de eletrodos compósitos quimicamente modificados com hidróxido e fosfato de cátions metálicos para determinação voltamétrica de analitos de interesse alimentício e farmacêutico - Freitas, Kellen Heloizy Garcia (2009)
The construction and evaluation of three modified carbon composite electrode (MCCE): MCCE-Cu3(PO4)2, MCCE -Ni(OH)2 and MCCE-resin-Cu(II) are described. These electrodes were applied for the determination of antioxidants in some food samples as teas, mayonnaise and margarine and in pharmaceutical formulations using: cyclic voltammetry (CV), linear sweep voltammetry (LSV) and square wave voltammetry (SWV). Several parameters were investigated such as: carbon composite composition, supporting electrolyte used in each determination, concentration of electrolyte, pH, solubility of the samples, besides the instrumental parameters for the technique used: cyclic voltammetry to get information about reversibility of the systems and mass transference (scan rate), parameters of square wave voltammetry (square wave frequency, square wave amplitude and sweep increment), and linear voltammetry (scan rate), both used for quantification of the antioxidants studied. The first electrode developed was MCCE with Cu3(PO4)2 immobilized in a polyester resin. The best voltammetric response was observed in a composite composition of 40% (m/m) of Cu3(PO4)2, 40% (m/m) of graphite powder and 20% (m/m) of paraffin solid; 0.10 mol L-1 phosphate buffer (conditional pH 6.8) as the supporting electrolyte containing 5, 20 and 10% of ethanol (v/v) for determination of natural antioxidants: catechin (CAT), quercetin (QCT) and rutin (Rut) respectively. This electrode was also applied in the determination of artificial antioxidants BHA and BHT in the following conditions: 0.10 mol L-1KNO3 (pH 6.7) containing 10% of ethanol (v/v) as the supporting electrolyte, with good analytical performance. The analytical curves obtained for all the determinations showed a good linear response in the concentration range around two decades and detention limits of magnitude 10-7 mol L-1 for Rut and 10-8 for the other antioxidants. The second electrode proposed was MCCE with Ni(OH)2 immobilized in a polyester resin for determination of natural and artificial antioxidants already mentioned. The best voltammetric response was observed in a composite composition of 20% (m/m) of Ni(OH)2, 60% (m/m) of graphite powder and 20% (m/m) of paraffin solid; 0.05 mol L-1 phosphate buffer (conditional pH 6.9) as the supporting electrolyte containing 5, 20 and 10% of ethanol (v/v) for determination of CAT, QCT and Rut respectively. For the determination of BHA and BHT, the conditions were: 0.10 mol L-1 KNO3 (pH 6.7) containing 10% of ethanol (v/v) as the supporting electrolyte for both. The analytical curves obtained for all the determination of antioxidants showed a good linear response in the concentration range around two decades and detention limits of magnitude 10-7 mol L-1 for QCT, Rut and BHA and 10-8 for CAT and BHT. The results obtained by proposed methods were compared with the results obtained by HPLC and the relative errors were less than 5% for all the determination using MCCECu3( PO4)2 and MCCE-Ni(OH)2. Student s t-test was applied for the results obtained for each antioxidants investigated. The results showed good accuracy of the methods. According to the t-test, the texperiment was less than tlabel, thus there are not significant differences between the results obtained by either procedure at 95% confidence level. Finally, a cationic exchange resin modified with Cu2+ ions was used as modifier material in a CCEM, which was applied in the voltammetric determination of rutin. The analytical curve was linear in the rutin concentration range 9.90 x10−7 and 8.07 x 10−6 mol L−1, with a detection limit of 2.65 x 10-7 mol L-1. In this work was pointed out the increase in the selectivity of proposed electrodes for antioxidant determination in food samples and pharmaceutical formulations, due to the decrease of work potentials observed to proposed CCEMs for each antioxidant investigated in comparison to the ones obtained for the same antioxidant using a not modified CCE.